Test Quick Submit - Bambang Wahyudi (Students Journal, 2015)
Ttest ----------The number of features obtained are much smaller than the number of pixels the image size 22500 (150x150). Then features obtained are used to train SVM classifiers. The first testing phase measures the accuracy of the detection process without sliding windows. The second testing phase use sliding windows to detect the occurance of dual tires in an image. For the first phase testing, we use a database that consists of 552 dual tires images and 1284 non dual tire images with 150 x 150 pixels, and for the second phase testing, we used data citra dari frame-frame video berukuran 800x450 pixels.